2019
DOI: 10.4103/jnrp.jnrp_329_18
|View full text |Cite
|
Sign up to set email alerts
|

Ventriculoperitoneal Shunt Disconnection, Shunt Migration, and Silent Bowel Perforation in a 10-Year-Old Boy

Abstract: A 10-year-old boy was admitted with chest wall infection around the implanted ventriculoperitoneal shunt (VPS) catheter of 5 days. He had received a right-sided, medium pressure, whole-length VPS for hydrocephalus, following tubercular meningitis at the age of 3 years. Seven years, 9 months following VPS implantation, he was admitted with shunt tract infection at the chest area for 5 days. He had neither fever nor features of meningitis, raised intracranial pressure, or peritonitis. His clinical examination an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…In addition, In addition, there was a high rate of infection with percutaneous subdural puncture (25%) [34]. 0-12% of patients recurred after SPS and 8-36% of cases had postoperative complications [35][36][37][38]. Previous reports had indicated that 38-93% of cases require removal of the shunt after SPS and the burr-hole craniotomy performed had a higher rate of single operation success than SPS [32,38].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, In addition, there was a high rate of infection with percutaneous subdural puncture (25%) [34]. 0-12% of patients recurred after SPS and 8-36% of cases had postoperative complications [35][36][37][38]. Previous reports had indicated that 38-93% of cases require removal of the shunt after SPS and the burr-hole craniotomy performed had a higher rate of single operation success than SPS [32,38].…”
Section: Discussionmentioning
confidence: 99%
“…[33] Clinical presentation SCMPA is a rarer cause of cardiopulmonary shunt migration, where the catheter migrates to the pulmonary vasculature. [7,11,18,19,36] Patients with SCMPA usually develop signs and symptoms of increased ICP, including headaches, mental status changes, focal neurological deficits, and vomiting. In contrast, SCMPA patients with concurrent arterial thrombosis usually present with the right heart strain symptoms, such as, dyspnea, chest pain, exertion, and coughing in the emergency setting with signs of respiratory failure.…”
Section: Discussionmentioning
confidence: 99%
“…[7] VP shunt complications include catheter obstruction, infection, system disconnection, hardware failure, and pseudocyst formation. [11,31] Less commonly, VP shunt catheters may migrate into ectopic sites, including the bowels, bladder, abdominal wall, thoracic cavity, and cardiovascular system. [18] Distal VP shunt catheter migration into the pulmonary artery (SCMPA) with concurrent large vessel thrombosis is an extremely rare occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…One of the issues that can lead to distal catheter disconnection from a straight connector is repeated cervical motion. 4 The downward and shearing forces create mechanical stress that, over time, lead to degradation in the structural integrity of the shunt. 5 Angular forces applied at the proximal end of the shunt create a significant amount of tension that is communicated to the straight connector.…”
Section: Discussionmentioning
confidence: 99%